Customer Accounting and Environmental Uncertainty: Sequential Explanatory Study - Al-Mawali, Hamzah; Lam, Tri-Dung (International Review of Management and Marketing, 2016)
This study seeks to substantiate its proposition through two research objectives: (1) to investigate the impact of CA information usage on companies’ performance; and (2) to determine the moderating effect of PEU on the relationship between CA information and companies’ performance. This study develops a theoretical framework by applying interaction fit . To answer the research questions, the study follows a sequential explanatory design and the data is collected in two phases. In the first phase, 172 questionnaires are distributed to managers, of which 97 questionnaires are deemed usable. The results of this stage indicate that CA information usage significantly influences organizational performance, and that there is a moderating effect of PEU on the relationship between CA information and organizational performance. The second phase aims to validate the quantitative results via seven semi-structured interviews. The results of the interviews confirm and explain those obtained from the first phase. Keywords: Customer Accounting information, Organizational Performance, Perceived Environmental Uncertainty JEL Classifications: M41; M42; M48